2016
DOI: 10.1071/wf15130
|View full text |Cite
|
Sign up to set email alerts
|

Towards a new paradigm in fire severity research using dose–response experiments

Abstract: Most landscape-scale fire severity research relies on correlations between field measures of fire effects and relatively simple spectral reflectance indices that are not direct measures of heat output or changes in plant physiology. Although many authors have highlighted limitations of this approach and called for improved assessments of severity, others have suggested that the operational utility of such a simple approach makes it acceptable. An alternative pathway to evaluate fire severity that bridges fire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
89
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 74 publications
(97 citation statements)
references
References 52 publications
6
89
1
1
Order By: Relevance
“…The strong relationship between dNDVI and PN observed in these fire dose-response experiments supports the methodology of [8] and further demonstrates that spectral indices have the potential to improve burn severity quantification through the monitoring of plant physiological metrics. While many studies have tested the utility of spectral indices for quantifying broad burn severity metrics (i.e., canopy cover, soil color, etc.)…”
Section: Discussionsupporting
confidence: 63%
See 4 more Smart Citations
“…The strong relationship between dNDVI and PN observed in these fire dose-response experiments supports the methodology of [8] and further demonstrates that spectral indices have the potential to improve burn severity quantification through the monitoring of plant physiological metrics. While many studies have tested the utility of spectral indices for quantifying broad burn severity metrics (i.e., canopy cover, soil color, etc.)…”
Section: Discussionsupporting
confidence: 63%
“…The results of this and the prior studies [8] demonstrate that at one month post-fire a clear dose-response relationship between FRED and ecophysiology metrics is apparent. This study demonstrated that at one year post-fire the surviving seedlings of the 0.4 MJ¨m´2 and 0.8 MJ¨m´2 treatments were not significantly different from the control.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations